Vold, køn og kultur – en etnografisk tilgang - Sofie Danneskiold-Samsøe (The Royal Danish Library, 2017)
Violence, gender and culture – an ethnographic approach. This article explores how an ethnographic approach to the study of violence against women (VAW) can provide insight into a particular gender culture with particular gender logic(s). The empirical data come from a study the authors have done on VAW in ethnic minority families in Denmark. The analytical framework consists of four analytical perspectives: the perception of violence, the continuum of violence, the triangle of violence and the context of violence. The main findings are: An ethnographic approach contributes with a unique ‘insider’ perspective, which makes it possible to get insight into the gender-cultural logic(s) of violence while putting these into play with general features of VAW and ethnographic context. VAW emphasizes a particular gender order by disciplining women. In that sense violence serves as an arena for the construction of gender.